Sensitive analysis of livestock breeding production on family farms - Subić, Jonel; Ivanović, Lana; Jeločnik, Marko (Economics of Agriculture, 2010)
In process of transition of national economy into market economy, agricultural husbandries are adjusting their business activities to suit new economic conditions. So, their goals have shifted significantly: from self-sufficiency towards increased production for market and realization of principles of own profitability. As very complex process, live stock breeding production requires from agriculturalist constant decisions making related to maintaining, or increasing of gained profit on farm. Making of right and timely decisions, is closely related to the possession of appropriate knowledge and skills, necessary information, as well as with proper perceiving and solving of appeared problems. In livestock breeding production the significant source of risks is permanent growth of production costs, parallel with products prices fall. Hence, it is important to consider the risk of certain productions, where sensitive analysis could provide relevant information. In paperwork are analyzed economic effects of different livestock breeding productions in terms of yields, prices and costs change. On that way is possible to notice which factors affect the most on economic effects within production, as well as which production is more risky.